New sources of resistance in sorghum (Sorghum bicolor) germplasm are effective against a diverse array of Potyvirus spp. - Seifers, Dallas L.; Perumal, Ramasamy; Little, Christopher R. (My University, 2012)
Sorghum is a host to numerous Potyvirus spp. and its germplasm encompasses a wide range of infection responses to these viruses. We determined how 183 mini-core-collection sorghum germplasm accessions responded to mechanical inoculation with Maize dwarf mosaic virus (MDMV) in growth regimes in which they were maintained at 30°C followed by 16°C for 5 days. Accessions that appeared immune to MDMV in this initial screening were evaluated for their response in a similar temperature maintenance regime to mechanical inoculation with MDMV, Sugarcane mosaic virus strain MDB (SCMV-MDB), Sorghum mosaic virus (SrMV), Zea mosaic virus (ZeMV), and Kansas, Nigerian, and Australian isolates of Johnsongrass mosaic virus (JGMV-KS, -N, and -Aus, respectively). In both experiments, MDMV systemically infected all accessions except international sorghum accession number (IS) 7679 and IS 20740. These accessions also proved resistant to MDMV, SCMV-MDB, SrMV, and JGMV-N but both were susceptible to the JGMV-KS and JGMV-Aus isolates. IS 7679 but not IS 20740 was resistant to infection with ZeMV. These observations suggest that IS 7679 and IS 20740 might serve as new sources of resistance to several Potyvirus spp. that systemically infect sorghum.
Citation: Seifers, D., . . . , Little, C. (2012). New Sources of Resistance in Sorghum (Sorghum bicolor) Germplasm Are Effective Against a Diverse Array of Potyvirus spp. Plant Disease, 96(12), 1775-1779. https://doi.org/10.1094/PDIS-03-12-0224-RE
Keywords: Sorghum; Sorghum bicolor; Potyvirus spp.; Germplasm; Maize dwarf mosaic virus; Sugarcane mosaic virus; Sorghum mosaic virus; Zea mosaic virus; Johnsongrass mosaic virus